Pengaruh Yoga terhadap Gangguan Tidur Insomnia - Pramesti, Mediska Arta (Universitas Malahayati, 2023)
ABSTRACT Sleep is a need for every human being. Non-organic sleep disorders including dyssomnias and parasomnias. Dyssomnia is a primary psychogenic condition in which the main disturbance is the amount, quality or timing of sleep caused by emotional issues, for example: insomnia, hypersomnia, disturbed sleep-wake schedule. In Indonesia, the prevalence rate of insomnia is around 67%. Meanwhile, 55.8% had mild insomnia and 23.3% had moderate insomnia. The use of mindfulness-based therapies for insomnia, which are based on mindfulness mediation, guided imagery, and biofeedback, can also be incorporated into treatment. By doing yoga, especially breathing techniques or pranayama, it can make a person more focused, calm the mind, reduce stress levels, give a feeling of calm and comfort to the body, so it is hoped that it can overcome insomnia. Keywords: Yoga, Sleep Disturbance, Insomnia ABSTRAK Tidur adalah kebutuhan setiap manusia. Gangguan tidur non-organik termasuk dyssomnia dan parasomnia. Dyssomnia adalah kondisi psikogenik primer dimana gangguan utamanya adalah jumlah, kualitas atau waktu tidur yang disebabkan oleh hal-hal emosional, misalnya: insomnia, hipersomnia, gangguan jadwal tidur-jaga. Di Indonesia, angka prevalensi insomnia sekitar 67%. Sedangkan sebanyak 55,8 % insomnia ringan dan 23,3 % mengalami insomnia sedang. Penggunaan terapi berbasis mindfulness untuk insomnia, yang didasarkan pada mediasi mindfulness, citra terbimbing, dan biofeedback, juga dapat dimasukkan ke dalam pengobatan. Dengan melakukan yoga, terutama teknik olah napas atau pranayama, membuat seseorang menjadi lebih fokus, menenangkan pikiran, menurunkan tingkat stress, memberikan perasaan tenang dan nyaman pada tubuh, sehingga diharapkan dapat mengatasi insomnia. Kata Kunci: Yoga, Gangguan Tidur, Insomnia